Discussion on Islamic Finance and Small Medium Enterprises’ Financial Accessibility - Hassanudin Mohd Thas Thaker; Chandra Sakaran Kanan (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
This study attempts to provide insights on SMEs’ financial accesibility through Islamic finance and its successfulness in Malaysia. The innovation in the Malaysia financial landscape especially Islamic finance has benefits the SMEs in accessing financial assistance without rely on traditional mode of financing. SMEs in Indonesia represent about 99 percent in all economic sector and involved labor participation of almost 95 percent but the issue of financial accessibility remain perpetual problem and block the development of SMEs in Indonesia. Therefore, the present study utilizes content analysis to critically look at the successful of SMEs Islamic financing in Malaysia and various published report and literature in generate better overview on the progression of SMEs. At the end of the study, this study provides some recommendations based on Malaysian SMEs financing successfulness for Indonesian authority to further restructure and enhance their existing financial assistance to the SMEs based on Islamic financing.